2020
DOI: 10.3390/app10238380
|View full text |Cite
|
Sign up to set email alerts
|

Improved Performance in the Detection of ACO-OFDM Modulated Signals Using Deep Learning Modules

Abstract: Free space optical communication (FSO) is widely deployed to transmit high data rates for rapid communication traffic increase. Asymmetrically clipped optical orthogonal frequency division multiplexing (ACO-OFDM) modulation is a very efficient FSO communication technique in terms of transmitted optical power. However, its performance is limited by atmospheric turbulence. When the channel includes strong turbulence or is non-deterministic, the bit error rate (BER) increases. To reach optimal performance, the AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Panda and Bhanja (2021) reported an improved performance evaluation of OFDM-FSO scheme by designing a modified OFDM receiver. In the previous works reported in (Sharma, 2014;Patel et al, 2014;Nistazakis et al, 2016;Attri et al, 2017;Zhang et al, 2018;Ajewole et al, 2019;Gupta et al, 2019;Hario et al, 2019;Darwesh and Kopeika, 2020;Panda and Bhanja, 2021) single-channel OFDM transmission has been discussed over free-space channel. Further enhancement of transmission capacity of FSO can be achieved by employing more OFDM channels transmission simultaneously which can be achieved using Wavelength-Division Multiplexed (WDM) transmission.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Panda and Bhanja (2021) reported an improved performance evaluation of OFDM-FSO scheme by designing a modified OFDM receiver. In the previous works reported in (Sharma, 2014;Patel et al, 2014;Nistazakis et al, 2016;Attri et al, 2017;Zhang et al, 2018;Ajewole et al, 2019;Gupta et al, 2019;Hario et al, 2019;Darwesh and Kopeika, 2020;Panda and Bhanja, 2021) single-channel OFDM transmission has been discussed over free-space channel. Further enhancement of transmission capacity of FSO can be achieved by employing more OFDM channels transmission simultaneously which can be achieved using Wavelength-Division Multiplexed (WDM) transmission.…”
Section: Literature Surveymentioning
confidence: 99%
“…The authors reported faithful 10 Gbps-2 km transmission for sunny climate with favourable SNR at the demodulator. Darwesh and Kopeika (2020) reported the improvement in the detection mechanism of asymmetrical clipped optical-OFDM signals in a FSO scheme by employing deep learning techniques. Panda and Bhanja (2021) reported an improved performance evaluation of OFDM-FSO scheme by designing a modified OFDM receiver.…”
Section: Literature Surveymentioning
confidence: 99%
“…DCO-OFDM is considered as one of the simplest and earliest MCM techniques to be compatible with IM/DD systems by generating a real and non-negative-valued OFDM scheme. It involves adding DC-bias to the signal which is supposed to be in unipolar format [9,10]. The block diagram of DCO-OFDM is shown in Fig.…”
Section: Dco-ofdmmentioning
confidence: 99%
“…Unevenly Clipped Optical Orthogonal Frequency Division Multiplexing (ACO-OFDM) modulation is one of the strategies that can change over the transmitted signals to be bipolar and genuine without any loss of the transmission data [40]. It is proficient in terms of optical power for lower SNR values for the IM/DD channel [41].…”
Section: Aco-ofdmmentioning
confidence: 99%